Measurements of the Cosmic Microwave Background Temperature at high redshift by analysis of CO excitation. (November 2015) - Sobolev, A I; Ivanchik, A V; Varshalovich, D A; Balashev, S A
Abstract: The linear relation between the temperature of the Cosmic Microwave Background and the cosmological redshift is a fundamental prediction of the standard hot Big Bang model. Measurements of the CMB temperature in the past can be done by means of observing radiative excitation of atomic and molecular species like C and CO. It can be detected in quasar spectra with z ∼ 2. We study excitation of CO rotational levels both by the CMB radiation and collisions. Corrections of determination of the CMB temperature due to collisional excitation by the analysis of CO molecule rotation level populations are proposed.